On the Phase Response and Radiation Efficiency of the Complementary Strip-Slot as an Array Element - Abdo-Sánchez, María Elena; Martín-Guerrero, Teresa María; Esteban Marzo, Jaime; Camacho-Peñalosa, Carlos (My University, 2015)
The complementary strip-slot element is a broadlymatched microstrip radiator that has been used to design innovative series-fed arrays. It consists of a microstrip series-fed slot that have its complementary stub on the layer of the microstrip and aligned to the slot. In this contribution, the influence of the strip and slot geometry on its performance is studied through the analysis of four different designs. The obtained results highlight the possibility of controlling the radiation efficiency or the phase response, without compromising the broad matching. Therefore, potential series-fed arrays built with this element can exploit this feature to set the magnitude and phase of the excitations with certain flexibility.
Keywords: Comunicaciones; Array; Microstrip; Series-fed; Strip-slot